Draft genome sequence of a multidrug-resistant Acinetobacter baumannii ST15 (CC15) isolated from Brazil - Thiago Pavoni Gomes Chagas; Melise Chaves Silveira; Rodolpho Mattos Albano; Ana Paula D’Alincourt Carvalho-Assef; Marise Dutra Asensi (Memorias do Instituto Oswaldo Cruz, 2015)
Acinetobacter baumannii is an important pathogen frequently associated with nosocomial outbreaks around the world. In Brazil, A. baumannii has become particularly problematic because of its prevalence and the carbapenems resistance. Here, we report the draft genome sequence of a multidrug-resistant A. baumannii (ST15/CC15) isolated in 2009 from the state of Espírito Santo (Southeast Brazil). We observed important resistance determinant genes in an estimated genome size of 4,102,788 bp with 3,862 predicted coding regions. A detailed report of the genomic data analysis might help to understand the specific features of highly successful strains belonged to a relevant complex clonal in different Brazilian geographical regions.